Peripheral Inflammation Enhances Microglia Response and Nigral Dopaminergic Cell Death in an in vivo MPTP Model of Parkinson’s Disease - García-Domínguez, Irene; Veselá, Karolina; García-Revilla, Juan; Carrillo-Jiménez, Alejandro; Roca-Ceballos, María Angustias; Santiago, Marti; de Pablos, Rocío M.; Venero, José L. (Frontiers in Cellular Neuroscience, 2018)
The direct implication of systemic inflammation in triggering dopaminergic cell loss under disease conditions remains unclear. Here, we investigated the role of peripheral inflammation triggered by systemic lipopolysaccharide (LPS) in the Parkinson’s disease model based on the injection of the neurotoxin MPTP. Brain inflammation, microglia and astroglia activation, disruption of the blood brain barrier (BBB) and integrity of the nigrostriatal dopaminergic system were evaluated in response to systemic LPS, MPTP or the combination of both. Our results show that combined systemic LPS and MPTP, as compared with MPTP alone, accelerates the onset of microglia activation, and enhances i) the appearance of galectin-3-positive microglia, recently identified as microglial disease-associated phenotypic marker, ii) up-regulation of pro-inflammatory markers, iii) the occurrence of A1 neurotoxic astrocytes, iv) the breakdown of the BBB, and v) the loss of dopaminergic neurons in the substantia nigra. Microglia activation occurred earlier than degenerative events, suggesting that over-activation of microglia (including different polarization states) can trigger dopaminergic loss by itself, initiating the endless cycle of inflammation/degeneration. Our study revitalizes the importance of peripheral inflammation as a potential risk factor in Parkinson´s disease and raises the possibility of using new therapies to improve the course of neurodegenerative diseases, including those aimed directly to modulate the deleterious activity of pro-inflammatory microglia.